On the Synthesis of a Linear Quadratic Controller for a Quadcopter - Hendra Gunawan Harno (Universitas Sanata Dharma, 2019)
This paper discusses about synthesizing a state-feedback controller for a quadcopter based on an optimal linear quadratic control method. The resulting flight control system enables the quadcopter to maintain stability and to track a reference input. The solution to this control problem involves solving an algebraic Riccati equation. The reference-input tracking capability is simulated to show the capability of the quadcopter flight control system.